(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
Crop diversification is a strategy used by producers to address their household food insecurity. This study analyzes the factors that influence households’ decision to participate in crop diversification on their plot and the determinants of the level of diversification based on survey data obtained through stratified sampling in the Tonkpi, Poro and Tchologo regions in 2020. The Herfindahl index was used to classify producers according to their degree of crop diversification. Applying the Cragg hurdle regression, the study shows that the decision to diversify crops is positively associated with household size, group membership, male gender, number of farm equipment, access to formal credit, distance from town, and region of residence of the producer and negatively associated with producer age and distance from the plot. The degree of diversification is positively associated with group membership and access to formal credit. The results therefore suggest policies to facilitate access to credit and to train and supervise producer groups in rural areas.